Evaluation of oxidative stress markers and intra-extracellular antioxidant activities in patients with endometriosis. (April 2016) - Turkyilmaz, Esengul; Yildirim, Melahat; Cendek, Busra Demir; Baran, Pervin; Alisik, Murat; Dalgaci, Ferit; Yavuz, Ayse Filiz
Abstract: Objective: The aim of the study is to evaluate alterations in intracellular and extracellular antioxidant enzymes activities and serum oxidative stress markers in patients with endometriosis. Study design: The current prospective study consisted of 31 female patients with endometriosis and 27 healthy controls. Serum total thiol, native thiol, disulphide, catalase, myeloperoxidase, and ceruloplasmin concentrations were measured. Laboratory and clinical data of all participants were recorded to compare the differences between the study and the control groups. Results: Serum native thiol and total thiol levels in the study group were significantly lower than those in the control group [( p  = 0.009, p  = 0.03, respectively)]. Serum catalase levels are significantly higher in patients with endometriosis comparing to the control group ( p  = 0.009). Conclusions: The finding that significant differences in serum total thiol, native thiol, and catalase levels observed in endometriotic patients supports that oxidative stress carries weigh in the pathophysiological aspects of endometriosis. Also significantly low levels of extracellular antioxidants and significantly high levels of intracellular antioxidants in endometriotic patients may arise from differences of free radicals in endometriosis and the activity levels of endometriosis. These non-invasive serum markers might give us an opportunity to monitor the disease's progress during the treatment.